Anti-Seizure Medication Treatment of Benign Childhood Epilepsy With Centrotemporal Spikes: A Systematic Review and Meta-analysis - Cheng, Wenwen; Yang, Yan; Chen, Ying; Shan, Sharui; Li, Changhui; Fang, Ling; Zhang, Weiguo; Lan, Song; Zhang, Xiong (Frontiers in Pharmacology, 2022)
Background: This study aimed to evaluate the efficacy and tolerability of Anti-Seizure medication (ASM) treatment in patients with BECTS. Method: We searched PubMed, Cochrane Library, Embase, MEDLINE, Web of Science, China National Knowledge Infrastructure (CNKI), WANFANG DATA, and China Science and Technology Journal Database (VIP) between Jan 1, 1990, and Sep 1, 2021, for randomized controlled studies. Data on seizure freedom rate, rate of treatment withdrawal due to serious adverse events, rate of any adverse events and dropout, 50% remission rate, the proportion of patients whose EEG to be normalized, and improvement in cognitive function were extracted by two authors independently. The pooled data were meta-analyzed using a random effects model. Results: A total of 27 studies evaluating 9 ASMs were included, 19 of which were suitable for meta‐analysis. Compared with sulthiame (STM), levetiracetam (LEV) was associated with a higher probability of treatment withdrawal due to serious adverse events (RR=5.12, 95% CI [1.19, 22.01], I2=0.0%), experiencing any adverse events (RR=5.12, 95% CI [1.19, 22.01]), and dropping out for any reason (RR=3.17, 95% CI [1.36, 10.11]), while it did not affect the seizure freedom rate (RR=0.90, 95% CI [0.75, 1.06]). LEV significantly improved cognitive performance relative to carbamazepine (CBZ) but had no effect on the proportion of any adverse events (RR=0.62, 95% CI [0.25, 1.59]) and EEG to be normalized (RR=1.27, 95% CI [0.94, 1.71]). There was no higher probability of a 50% remission rate when comparing valproic acid (VPA) to LEV (RR=0.96, 95% CI [0.57, 1.61]) and oxcarbazepine (OXC) (RR=0.61, 95% CI [0.31, 1.20]). In addition, STM was related to a higher probability of EEG normalization than placebo (RR=4.61, 95% CI [2.12, 10.01]). The included single studies also provided some evidence for the efficacy and/or tolerability of other ASMs in BECTS, including topiramate, lamotrigine, clobazam, and clonazepam. The risk of bias of the included studies was frequently low or unclear. Conclusion: This study indicated some discrepancies in efficacy and tolerability among ASMs used in patients with BECTS. More randomized controlled trials (RCTs) comparing ASMs with larger populations are required to ascertain the optimum antiepileptic drug treatment to guide clinicians.